Evaluation of Factors Affecting Quality of Nursing Cares for Dying Patients in ICUs - Mahnaz Varedi Kolahi1, Mohammad Ziae Totonchi Bagheri2, Hooman Bakhshandeh3, Reza Ghanei Gheshlagh4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Nursing managers have paid special attention to quality assessment as an important management tool for improving nursing performance and the quality of nursing care. This study aimed to evaluate the aspects and factors involved in the quality of nursing cares for dying patients in ICUs in 2016-7. This descriptive and analytical study was conducted in ICUs of Imam Khomeini Hospital Complex and Shahid Rajaei Cardiovascular Medical & Research Center, Tehran.In total, 191 working nurses were selected via convenience sampling. Data collection tool was quality patient care scale (QUALPACS). In addition, data analysis was performed in PSSS version 20 using descriptive and inferential statistics. The mean score for end-of-life care was 83.62±8.62 in the psychosocial, 85.36±7.74 in the communication and 92.23±10.88 in the physical aspects. According to the results, a significant relationship was observed between passing educational courses related to end-of-life care and quality of end-of-life care in the physical (P=0.002), psychosocial (P=0.02) and communication (P=0.01) aspects. According to the results of the study, the quality of care for dying patients was higher in the physical aspect, compared to other aspects. However, the quality of nursing care was poor in the psychosocial aspect.